SOLVING PROBLEMS IN THE PRESCHOOL EDUCATION SYSTEM AS THE MAIN STAGE OF THE EDUCATION SYSTEM - Karimova, Maftuna; Khurshid, Karimov (MMIT Proceedings, 2023)
The article examines the shortcomings and problems of preschool education processes and develops appropriate proposals for their resolution. The existence of problems in the placement of children in preschool educational institutions, the lack of provision for kindergartens and the measures taken in our country to eliminate them are considered. A study was conducted on this problem using the example of a preschool educational institution. Inclusion of children who have not yet entered kindergarten in the educational process in preschool educational institutions as a proposal to the article. Recommendations have been developed to increase the level of interest not only of educators, but also of parents in raising a child and creating a healthy environment in the family. The peculiarities of the upbringing of children in the family were revealed, the styles of family education, the peculiarities of the emotional development of a preschool child were studied.